Standar Internasional tentang “Governance” dan Pengaruhnya pada Praktek Domestik Suatu Negara - Ruru, Emmy Yuhassarie (UI Scholars Hub, 2005)
The emminent economic crisis in the past decade – in particular in Asia has signified a momentum for initiate financial reform as imposed by industrialized countries, with aims to promote resilience in international financial system, to install a pre-warning signal, and to enable to seek effective measures to resolve the financial turmoil in the future. The preventive measures among others is to encourage government policy makers to implement international standards of governance in its financial sector by method or regulation and best practices. Aside of that, globalization of international financial system inevitability brings the practice of trade and transactions across countries within its outreach, which eventually leads to domestic countries to absorb the international standards, either way.